Historiens de la Grèce franque. (Athènes)
1. cilt (viii, 484 sayfa)
Keywords: “150 years apart, Charles Du Cange (1610-1688) and Jean-Alexandre Buchon (1791-1846) outlined the epistemological contours of the field of study defined by Frankish and Latin expansion in medieval Greece. In their view, the period deserved to be detached from developments specific to the Latin East by observing the dynamics of power relations in the Balkans and the Adriatic. They constructed a narrative based on political and military history, centred on an aristocratic conception of history, which justified extensive genealogical investigations. Operating in different intellectual environments, they laid the foundation for future research in the field: while Du Conge rounded his erudition on the examination of manuscript sources available in France, Buchon extended his inquiries to Italian archives. To highlight their respective contributions, this volume brings together nineteen studies from symposia held at the University of Rouen-Normandie on 28 October 2022 and at the École française d'Athènes on 26-27 October 2023” --